Copper nanowire with enriched high‐index facets for highly selective CO2 reduction. Issue 1 (17th January 2022) - Han, Lu; Tian, Benqiang; Gao, Xiangxiang; Zhong, Yang; Wang, Shengnan; Song, Shuchang; Wang, Zhili; Zhang, Ying; Kuang, Yun; Sun, Xiaoming
Abstract: Electroreduction of carbon dioxide into fuels and feedstocks with renewable energy is an attractive route to mitigate carbon emission and solve energy crisis. However, how to improve the selectivity of high‐value multicarbon products is still challenging. Here, we demonstrate that the high‐index crystalline surface of copper could be designed and obtained through a simple square‐wave potential treatment on copper nanowires, which is beneficial to improve the selectivity of multi‐carbon products, especially the reaction route towards ethylene. The Faradaic efficiency of C2+ products can reach nearly 60%, and hydrogen can be suppressed to below 20%. Density functional theory (DFT) calculations reveal that (311) high‐index facet can activate CO2 effectively and promote adsorption of the *COCOH intermediate on copper for ethylene formation, therefore improves the selectivity of ethylene and inhibits the competing hydrogen evolution reaction. This method can be extended to the design of other catalytic systems and has inspirations for other electrochemical catalytic reactions. Abstract : High‐index facets have a positive effect on improving the performance of CO2 reduction reactions. The synthesis of Cu nanowires with high‐index facets is designed by square wave potential treatment. the FE of C2+ products (ethylene, ethanol, n‐propanol) of the copper catalyst with high‐index facets (~57%) is four times higher than that of the original Cu NWs (~13%) under optimal conditions.